2016
DOI: 10.1038/tp.2016.109
|View full text |Cite
|
Sign up to set email alerts
|

Elevated paternal glucocorticoid exposure alters the small noncoding RNA profile in sperm and modifies anxiety and depressive phenotypes in the offspring

Abstract: Recent studies have suggested that physiological and behavioral traits may be transgenerationally inherited through the paternal lineage, possibly via non-genomic signals derived from the sperm. To investigate how paternal stress might influence offspring behavioral phenotypes, a model of hypothalamic–pituitary–adrenal (HPA) axis dysregulation was used. Male breeders were administered water supplemented with corticosterone (CORT) for 4 weeks before mating with untreated female mice. Female, but not male, F1 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
183
6
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(203 citation statements)
references
References 86 publications
(126 reference statements)
11
183
6
3
Order By: Relevance
“…The paternal preconception environment modulates the RNA content of the developing sperm, with possible effects on post-fertilization development and offspring phenotypes 53 . In animal studies, paternal exposures to high-fat and high-sugar diets produce metabolic disturbances in offspring 54 , and both stress and exercise affect stress responses of the offspring [55][56][57] . Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…The paternal preconception environment modulates the RNA content of the developing sperm, with possible effects on post-fertilization development and offspring phenotypes 53 . In animal studies, paternal exposures to high-fat and high-sugar diets produce metabolic disturbances in offspring 54 , and both stress and exercise affect stress responses of the offspring [55][56][57] . Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…Moreover, in rodents, transgenerational inheritance of stress can modify the F2 phenotype without alterations in the F1 phenotype. We previously showed that paternal exposure to CORT had an effect on F2 depression-like behavior but not in F1, an effect that was transmitted through the male lineage (Short et al, 2016). Other studies have also indicated that phenotypes in the F2 or F3 generations differ from those seen in the F1 animals (Bygren et al, 2001;Franklin et al, 2010), although these phenotypes could be affected by the changes in the F1 generation.…”
Section: Paternal Environmental Enrichment Modifies F2 Despair Behavimentioning
confidence: 93%
“…Observations took place every 5 minutes for 60 minutes in every session and were manually scored as previously described (Chourbaji et al, 2011;Short et al, 2016). …”
Section: Maternal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, epigenetic inheritance of depression associated phenotypes has been shown in an animal study in which paternal stress induced traits were transmitted across generations with involvement of small noncoding RNA signals which were passed through the male germline [18].…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%